Efficient alkene hydrosilation with bis(8-quinolyl)phosphine (NPN) nickel catalysts. The dominant role of silyl-over hydrido-nickel catalytic intermediates. Issue 19 (4th May 2020) - Yang, Jian; Postils, Verònica; Lipschutz, Michael I.; Fasulo, Meg; Raynaud, Christophe; Clot, Eric; Eisenstein, Odile; Tilley, T. Don
Abstract : A cationic nickel complex of the bis(8-quinolyl)(3, 5-di- tert -butylphenoxy)phosphine (NPN) ligand, [(NPN)NiCl] +, is a precursor to efficient catalysts for the hydrosilation of alkenes with hydrosilanes under mild conditions and low catalyst loadings. Abstract : A cationic nickel complex of the bis(8-quinolyl)(3, 5-di- tert -butylphenoxy)phosphine (NPN) ligand, [(NPN)NiCl] +, is a precursor to efficient catalysts for the hydrosilation of alkenes with a variety of hydrosilanes under mild conditions and low catalyst loadings. DFT studies reveal the presence of two coupled catalytic cycles based on [(NPN)NiH] + and [(NPN)NiSiR3 ] + active species, with the latter being more efficient for producing the product. The preferred silyl-based catalysis is not due to a more facile insertion of alkene into the Ni–Si ( vs. Ni–H) bond, but by consistent and efficient conversions of the hydride to the silyl complex.